Tourism Space – the Cycle, the ‘Actors’ and Development Determining Factors - Włodarczyk, Bogdan (Turyzm/Tourism, 2006)
The author discusses the issue of tourism space both from a subjective (individual and perceptive) and an objective point of view (the place or area of occurrence). He also discusses types of tourism space as regards the territory they occupy as well as dynamically, as potential development phases for tourism space. As a result, he proposes a tourism space development cycle. In addition, the roles of different groups of tourism space 'actors' and the factors determining organizaUon and functioning of tourism space are described. The author further proposes a model research procedure aiming at a full description of tourism space.